2013
DOI: 10.1016/s1734-1140(13)71072-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to alcohol and tobacco smoke causes oxidative stress in rats

Abstract: The obtained results suggest that in the ethanol-addicted rats combined exposure to smoke and alcohol differentially modulate endogenous antioxidant defense system and reactions to oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
(38 reference statements)
4
17
1
1
Order By: Relevance
“…In addition, it was reported that CAT activity decreased upon chronic ethanol consumption in a study [20]. However, another study showed that CAT activity was increased in rat liver [18]. In our study, the alcohol treatment significantly increased the activity of SOD and slightly decreased the activity of CAT, while treatment with lemon juice decreased the activities of SOD and CAT.…”
Section: Discussioncontrasting
confidence: 40%
“…In addition, it was reported that CAT activity decreased upon chronic ethanol consumption in a study [20]. However, another study showed that CAT activity was increased in rat liver [18]. In our study, the alcohol treatment significantly increased the activity of SOD and slightly decreased the activity of CAT, while treatment with lemon juice decreased the activities of SOD and CAT.…”
Section: Discussioncontrasting
confidence: 40%
“…At the same time, the antioxidant enzymes, including sod1, gshpx, and gshrd, represent the defense response to excessive free radicals. The effects of alcohol exposure on the activity or content of antioxidant enzymes are rather controversial in the literature, depending on the model, diet, amount, and time of alcohol feeding [32][33][34][35][36].…”
mentioning
confidence: 99%
“…SOD (a metalloenzyme) converts superoxide anion to hydrogen peroxide, and CAT catalyzes then hydrogen peroxide into molecular oxygen and water. The effects of alcohol exposure on the activity or content of SOD and CAT are rather controversial in the literature, as the activity or content of SOD and CAT might increase, not change, or decrease, depending on the model, diet, amount, and time of alcohol feeding [13,24,28,29]. In this study, the activity of SOD was stimulated in the model with respect to the control group, but CAT decreased.…”
Section: Resultsmentioning
confidence: 65%